A review on combustion and mechanical behaviour of pyrolysis biochar. (June 2022) - Shanmugam, Vigneshwaran; Sreenivasan, S.N.; Mensah, Rhoda Afriyie; Försth, Michael; Sas, Gabriel; Hedenqvist, Mikael S.; Neisiany, Rasoul Esmaeely; Tu, Yongming; Das, Oisik
Abstract: Biochar has unique physical and chemical properties, making it a viable and sustainable future generation material for a variety of applications. The applications include power generation, composite production, construction (as a reinforcement), and soil amendment. The inherent good mechanical and combustion (or fire) resistance properties of biochar are attractive, however, there are limited reports, despite its effects on bulk material properties being well-documented. Comprehending these innate properties of biochar is critical for tailoring the mechanical and fire properties of biochar-based materials and structures. Therefore, an attempt has been made in this article to garner and analyse literatures reported on the mechanical and combustion properties of biochar without being integrated with a material or structural system (e.g. composite). Biochar produced at high pyrolysis temperatures (>500 ℃) showed high fire resistance property, because of the absence of the volatile matters and development of strong C-C covalent bonds. The mechanical and combustion properties of biochar can be controlled by varying the biochar size, porous nature, and pyrolysis temperature. The information presented in this article is crucial and can be used as a guide to develop biochar-based materials and structures for mechanical and fire resistance applications. Graphical Abstract: ga1